“Making Robots Usable”: Empowering Care Professionals to Customize Social Robots in Care - Manavi, Mehrbod; Carros, Felix; Schwaninger, Isabel; Paluch, Richard; Randall, Dave; Krueger, Maximilian; Tufan, Ilayda; Wieching, Rainer; Tolmie, Peter; Mueller, Claudia; Wulf, Volker (International journal of social robotics, 2025)
While robotic systems in eldercare contexts continue to be a popular research topic, they are still not widely used in these settings. We argue that this is partly due to the absence of control and configuration options for end-users. This study reflects on the design of a smartphone app to tailor the use of robots to local needs. We investigated how care workers used the smartphone app to configure and control a Pepper robot to meet the individual needs of the care home’s residents. We developed and tested the app together with 23 participants from four different care facilities over two years. Ultimately, we implemented a feature allowing care workers to program the robot to meet residents’ individual needs without coding. Results indicate that the app enables care workers to provide residents with meaningful interactions with the robot. Our study shows that allowing care workers to control and develop the robot improves its perceived usefulness and overall use of the robot to both care residents and care workers.